HYDRODYNAMIC MODEL OF TEXTILE MATERIAL DESTRUCTION - SYNYUK, OLEG; FEDUKH, MYKOLA; YUNAS, YURIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article investigates the mechanism of hydrodynamic defibering of textile waste using cavitation effects. The inefficiency of traditional mechanical methods for disintegrating textile materials – such as knife mills and rotor-stator systems – is substantiated due to their high energy consumption and limited effectiveness when processing multilayered or heavily worn fabrics. The advantages of the hydrodynamic approach in an aqueous medium are demonstrated, especially through the application of cavitational treatment. This method, due to localized zones of high pressure and temperature generated by collapsing cavitation bubbles, ensures targeted destruction of the fibrous structure and facilitates deeper penetration into the textile mass. A detailed physical and chemical analysis of the cavitation phenomenon led to the development of a mathematical model describing the penetration of the cumulative jet – formed upon the collapse of a cavitation bubble – into the fibrous structure of the textile material. The model takes into account the dynamics of jet formation, the physical properties of the working suspension (including viscosity and density), as well as the geometric parameters of the cavitation insert. Analytical equations were derived to determine the jet’s penetration depth depending on the suspension characteristics, structural properties of the treated textile, and the plastic deformation parameters relevant to the material. Numerical simulation of the process was performed using finite element methods, which made it possible to identify critical technological regimes, deformation thresholds, and optimal operational parameters for effective defibering. The study revealed that effective destruction of the fibrous matrix is achieved when the velocity of the cumulative jet is maintained within the range of 200-1400 m/s, and the pressure inside the defibering channel is kept between 0.01 and 0.35 MPa, depending on the thickness and composition of the textile waste. Based on the obtained results, a set of practical recommendations was proposed for the design and optimization of industrial cavitation-based defibering equipment. These findings may be effectively applied in the development of sustainable textile waste recycling technologies, contributing to resource conservation and reduction of environmental impact.